A Culturalist Approach to the Concept of the Mediatization of Politics: The Age of "Media Hegemony". (25th June 2013) - Block, Elena
Abstract : This article rethinks the concept of the mediatization of politics from a culturalist perspective, rebuilding the concept through five arguments: the first two are focused on the symbolic dimension of the issue in the context of the naturalized hegemonic media; the third presents it as a conceptual tool helpful to study the way citizens increasingly interact with media technologies and forms to engage with politics; the fourth poses it as a state of affairs where individuals and groups develop cultural patterns of media connectivity that lead to politically mediatized situations; the last proposes this state of affairs as the "fourth age" of political communication: An age of media hegemony. Hugo Chávez's politically mediatized Venezuela serves as an illustration .